Implementasi Model Pembelajaran Inquiry dalam Meningkatkan Hasil Belajar Fikih - Mudhofar; Qodir Jaelani, Abdul (LP3M Universitas Al-Qolam Malang, 2023)
This research began with low learning outcomes in fiqh subjects, one of the factors causing this was the lack of use of learning models that were appropriate for students. In this research the author tries to apply the inquiry learning model in an effort to improve learning outcomes. The problem formulation is whether the implementation of the inquiry learning model can improve fiqh learning outcomes. The focus of this research is 1) How to apply the inquiry learning model in improving learning outcomes in fiqh subjects. 2) To find out the learning outcomes of the class X B MA Modern Al Rifa'ie fiqh subject by applying the inquiry learning model. In this research, the Classroom Action Research (PTK) method was carried out in 2 cycles. In collecting data, researchers used observation methods, test methods, interviews and documentation. Meanwhile, for the analysis, researchers used descriptive analysis techniques, namely in the form of data reduction, data presentation and verification. This research went through several stages, namely preparation, implementation, data analysis and reporting stage. The results of the research show that the implementation of the inquiry learning model in fiqh subjects has been carried out according to the steps of the inquiry learning model and is going quite well. Meanwhile, the results of implementing the inquiry learning model can improve student learning outcomes in the learning process. Key words: education; inquiry; improvement; learning outcomes; students